Accelerator-Level Parallelism: Charging computer scientists to develop the science needed to best achieve the performance and cost goals of accelerator-level parallelism hardware and software. - Hill, Mark D.; Reddi, Vijay Janapa (Communications of the ACM, 2021)
The authors discuss the need for a new branch of computer science to develop accelerator-level parallelism in both computer hardware and software. They mention various forms of parallel processing that already exist, present a case study of mobile systems on a chip that are starting to rely on accelerator-level parallelism, and examine how the science might proceed in the future.